Consistency tests for heteroskedastic and risk models - R. Pagan, Adrian; Sabau, Hernán (Estudios Económicos de El Colegio de México, 1992)
This paper considers a class of consistency tests for the specification of heteroskedastic and risk models. The tests are related to other procedures such as the conditional moment tests of Newey and Tauchen, Hausman's tests, White's tests, the variable addition Lagrange multiplier tests of Engle and Pagan, and the residual analysis of Pagan and Hall. The power of the consistency tests in the presence of local departures is analyzed and the risk premia model of Engle, Lilien and Robins is re-assessed.